(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Microfinance institutions (MFIs) have become crucial engines of inclusive finance in India, empowering low-income entrepreneurs who lack collateral for formal credit. Yet their sustainability depends on borrowers’ repayment discipline. This study empirically examines socio-economic determinants influencing loan-repayment performance among microfinance clients in Bangalore Rural District, Karnataka. Using a structured questionnaire administered to 200 borrowers drawn from SKDRDP, Spandana, and Grameen Koota, the study evaluates the influence of income, education, business experience, loan size, financial-literacy training, and group-lending participation on repayment outcomes. Descriptive statistics, correlation, and multiple-regression analysis (SPSS 28.0) were used to identify significant predictors. Findings reveal that education level, household income, financial-literacy training, and group-lending membership significantly enhance repayment, whereas larger loan size slightly increases default probability. The study recommends borrower-capacity building, flexible repayment schedules, and digital tracking to ensure institutional sustainability.